Technical Reports of Endoscopic Retrograde Cholangiopancreatography Guidewires on the Basis of Physical Properties - Chang-Il Kwon; Dong Hee Koh; Tae Jun Song; Won Suk Park; Dong Hang Lee; Seok Jeong (Clinical Endoscopy, 2020)
Background/Aims Using an appropriate guidewire can increase the success rate of selective cannulation in endoscopic retrograde cholangiopancreatography. The purpose of this technical study was to investigate the characteristics of each guidewire type and to evaluate its efficiency and rapidity of insertion. Methods We conducted a three-point bending test using a universal testing machine to investigate the flexibility and bending features of each guidewire. 3D-printed silicone tubes with various types of stricture and a hand-made biliary tree silicone model with six-stranded intrahepatic ducts were used to evaluate the success rate and insertion time of each guidewire. Results In the three-point bending test, the characteristics of each guidewire were classified. We found that the bending strengths and times were independent of shaft thickness. Using two in vitro biliary duct models, we determined that the success rate and total insertion time were better for guidewires with a resilient shaft and angled tip than for other types of guidewires (p<0.001). Although thickness of the guidewire affected the success rate (p<0.05), it did not affect the total insertion time (p≥0.05). Conclusions Among several types of guidewire, some factors (resilient shaft, highly flexible, and angled tip) appeared to be associated with the efficiency and rapidity of the guidewire insertion.